Clinical, microscopic and mechanical evaluation of cutaneous tissue expansion in rats and dogs using immediate and gradual tissue expansion techniques - Ali, Ahmed Khalaf (2018)
Tissue expansion is a technique used to stimulate the body to grow additional tissues, allowing coverage of a variety of complex wounds. In 1957, Neumann was the first to describe the clinical soft tissue expansion when an air filled rubber balloon was implanted subcutaneously to reconstruct an ear after traumatic ablation. This technique was improved by Radovan and Argenta in 1970 when they used saline solution to inflate a silicon balloon gradually via a filling port located subcutaneously. This device was highly standardized and different shapes and sizes are now available to fit various indications. A selfinflation model was described by Austad and Rose in 1982. The generation of clinically and physically viable expanded skin produced by Immediate or gradual expansion technique is possible in laboratory and small animals with reduced complications rate where careful planning of tissue expansion as well as attentive post-operative care are followed. The aim of this study was to examine the effects of immediate and gradual rate of mechanical expansion of limb skin tissue using an expansion technique in rats and dogs. The specific objectives were: (1) to evaluate clinically the expanded tissue following immediate or gradual skin tissue expansion. (2) to study the histological aspects of the cutaneous tissue following immediate or gradual skin tissue expansion. (3) to assess the mechanical properties of the expanded tissue caused by immediate or gradual skin tissue expansion. (4) to test the presence and evaluate the expression of the vascular endothelial growth factor (VEGF) in the immediately and gradually expanded skin tissue rats and dogs. Immediate tissue expansion has been studied using different sizes of constant rectangle shaped tissue expanders made of polymethylmethacrylate (PMMA) which were surgically implanted under the subcutaneous tissue layer at the metacarpal area in dogs and metatarsal area in rats. Round and rectangle shaped self-inflating hydrogel tissue expanders were surgically implanted at the same site in dogs in different individual animals to evaluate gradual skin tissue expansion. Immediate skin tissue expansion of the metatarsal area was performed in four groups of rats (6 animals/ group), using four different sizes of the PMMA expanders. In dogs, the immediate skin tissue expansion of the metacarpal area was induced using three different sizes of the PMMA expanders in three groups of dogs (6 animals/ group). Immediate expansion procedure lasted for 14 days following implantation of the tissue expander in both rats and dogs. To induce gradual skin expansion of the metacarpal area, two groups of dogs (6 animals/ group) were used using round and rectangle self-inflating tissue expanders. The skin expansion process lasted for 30 days following implantation of the tissue expander. Clinical, histological and mechanical studies were undertaken on the immediately and gradually expanded skin samples collected at various time points. In general, immediate and gradual expansion processes in rats and dogs were well tolerated and associated with mild to moderate pain with low complication rates. Furthermore, there was no difference in terms of color, texture and hair bearance between normal and expanded skin. The thickness of the expanded skin was greater than that of the normal skin due to formation of a vascular fibrous capsule around the expander. Many histological changes were encountered as a result of the expansion process such as increased thickness of epiderm, decreased thickness of derm, increased fibroblast and collagen synthesis, increased mitotic activity, neovascularization, parallel realignment fashion of collagen fibers and the hair follicles, with sweat glands and sebaceous glands being farther apart. The evaluation of the VEGF of the immediately and gradually expanded skin in both rats and dogs revealed significant increase of VEGF expression. On the other hand, mechanical property evaluations of both normal and expanded skin of rats and dogs showed a significant decrease of the tensile strength of the immediately and gradually expanded skin in rats and dogs except the gradually expanded skin where rectangle shaped self-inflating tissue expander was used. In conclusion, the immediate and gradual self-tissue expansion techniques in rats and dogs were able to provide a good and less invasive skin expansion to the animals, with minimal complications seen in the outcomes and producing viable and relatively normal additional skin tissues. It is potentially useful for surgical repair of relatively large skin wound defects. The gradual self-tissue expansion technique was significantly better than the immediate type in terms of complication rates, clinical toleration of the expansion process and the mechanical properties of the expanded skin. The histological and mechanical properties changes caused by immediate and gradual expansion seemed to have no deleterious effects on the structural and functional skin features.